Necessary Maximum Principle of Stochastic Optimal Control with Delay and Jump Diffusion (Communications in Mathematical Research, 2021)
In this paper, we have studied the necessary maximum principle ofstochastic optimal control problem with delay and jump diffusion.
Keywords: stochastic differential equation; jump diffusion; delay; necessary maximum principle.